2021
DOI: 10.1038/s41467-021-23411-6
|View full text |Cite
|
Sign up to set email alerts
|

Spurious North Tropical Atlantic precursors to El Niño

Abstract: The El Niño-Southern Oscillation (ENSO), the primary driver of year-to-year global climate variability, is known to influence the North Tropical Atlantic (NTA) sea surface temperature (SST), especially during boreal spring season. Focusing on statistical lead-lag relationships, previous studies have proposed that interannual NTA SST variability can also feed back on ENSO in a predictable manner. However, these studies did not properly account for ENSO’s autocorrelation and the fact that the SST in the Atlantic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 48 publications
3
43
1
Order By: Relevance
“…However, different from Park et al (2019), the present study suggested that the negative NTA SST anomalies could induce anomalous warm SST in the southeastern tropical Pacific via the local meridional circulation before the mid-1980s. In addition, Zhang et al (2021) recently indicated that the NTA-ENSO relationship is a one-way Pacific to Atlantic connection, which is different from the present study and other previous researches (Ham et al 2013;Wang et al 2017;Ding et al 2017). It means that the connections between the Pacific and Atlantic should be further studied.…”
Section: Summary and Discussioncontrasting
confidence: 98%
“…However, different from Park et al (2019), the present study suggested that the negative NTA SST anomalies could induce anomalous warm SST in the southeastern tropical Pacific via the local meridional circulation before the mid-1980s. In addition, Zhang et al (2021) recently indicated that the NTA-ENSO relationship is a one-way Pacific to Atlantic connection, which is different from the present study and other previous researches (Ham et al 2013;Wang et al 2017;Ding et al 2017). It means that the connections between the Pacific and Atlantic should be further studied.…”
Section: Summary and Discussioncontrasting
confidence: 98%
“…
El Niño-Southern Oscillation (ENSO) is the dominant mode of interannual climate variability in the tropics. The spatiotemporal characteristics of ENSO exhibit variations (Dieppois et al, 2021;Wittenberg, 2009) driven by chaotic atmosphere-ocean dynamics (Fedorov et al, 2003;Zhang et al, 2021) and sources of variability from outside the tropical Pacific (Meehl et al, 2001). Given the global reach of ENSO and its impacts (Diaz et al, 2001), understanding and predicting changes in ENSO is a major challenge for the scientific community.In the last decade, it has become evident that climate variability and changes in other ocean basins can affect the tropical Pacific and ENSO (Cai et al, 2019).
…”
mentioning
confidence: 99%
“…Compared to the specific mechanisms of ENSO for TNA SST, its feedback is still in debate. For example, Zhang et al (2021) has revisited the TNA-ENSO relationship by considering ENSO's autocorrelation within its internal cycle, indicating TNA SST may not be a precursor for ENSO. Therefore, there are more works to be done in this bilateral trans-basin teleconnection and its change under greenhouse warming.…”
Section: Conclusion and Discussionmentioning
confidence: 99%